2005
DOI: 10.1124/mol.105.014654
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potent Inverse Agonist at a Constitutively Active Mutant of Human P2Y12 Receptor

Abstract: Human platelets express two P2Y receptors: G q -coupled P2Y 1 , and G i -coupled P2Y 12 . Both P2Y 1 and P2Y 12 are ADP receptors on human platelets and are essential for ADP-induced platelet aggregation that plays pivotal roles in thrombosis and hemostasis. Numerous constitutively active G protein-coupled receptors have been described in natural or recombinant systems, but in the P2Y receptors, to date, no constitutive activity has been reported. In our effort to identify G protein coupling domains of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 57 publications
5
36
0
Order By: Relevance
“…P2Y 12 expressed in yeast showed a similar EC 50 value for MeS-ADP (EC 50 value, 6 nM; Fig. 1) as when expressed in mammalian cells ranging from low nanomolar to 25-80 nM concentrations (Zhang et al, 2001;Simon et al, 2002;Bodor et al, 2003;Zhong et al, 2004;Ding et al, 2006;Hoffmann et al, 2008). ADP was approximately 500-fold less potent to MeS-ADP, which is consistent with previous findings showing an approximately 30-fold to 1000-fold lower potency in mammalian cells (Zhang et al, 2001;Simon et al, 2002;Bodor et al, 2003).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…P2Y 12 expressed in yeast showed a similar EC 50 value for MeS-ADP (EC 50 value, 6 nM; Fig. 1) as when expressed in mammalian cells ranging from low nanomolar to 25-80 nM concentrations (Zhang et al, 2001;Simon et al, 2002;Bodor et al, 2003;Zhong et al, 2004;Ding et al, 2006;Hoffmann et al, 2008). ADP was approximately 500-fold less potent to MeS-ADP, which is consistent with previous findings showing an approximately 30-fold to 1000-fold lower potency in mammalian cells (Zhang et al, 2001;Simon et al, 2002;Bodor et al, 2003).…”
Section: Resultssupporting
confidence: 81%
“…For example, many b-blockers and atropine are inverse agonists at b1-adrenoceptors and muscarinic acetylcholine receptors, respectively (Thor et al, 2009;Baker et al, 2011). Therapeutically used P2Y 12 ligands are high-affinity antagonists, but inverse activity was described only for the experimental P2Y 12 blocker AR-C78511 (Vasiljev et al, 2003;Ding et al, 2006). AR-C78511 is a 2-alkylthio-substituted ATP analog but, in contrast to mant-dATP, has no modification at the 29 or 39 OH residues of the ribose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 A follow-up study also revealed that AR-C78511 had superior antiplatelet activity compared with a neutral antagonist (cangrelor) in transgenic mice expressing the same chimeric receptor. 56 Interestingly, AR-C78511, like ticagrelor, could not be docked to the 2MeSADP-bound conformation of the P2Y 12 R, seemingly because of its own bulky N6 substituents.…”
Section: Discussionmentioning
confidence: 96%